An Exploration into the Transformation of University Talent Cultivation Models and Connotation Construction in the New Era - Han, Peng; Syaifuddin; Fajar Rezeki Ananda (Journal of Educational Theory and Practice, 2026)
The new era has raised higher value expectations and more profound quality requirements for higher education. University talent cultivation is undergoing a comprehensive transformation from scale expansion to quality improvement, from knowledge-based to competency-based, and from one-way indoctrination to subjective construction. This transformation is by no means a mere change of methods, but a systematic reshaping involving educational philosophy, institutional frameworks, and cultural ecology. As the internal foundation of this transformation, connotation construction focuses on returning to the original essence of fostering virtue through education and the deep generation of a quality culture. This paper explores the logical path, core dimensions, connotation implications, coupling mechanisms, and practical dilemmas, revealing the dialectical relationship in which model transformation and connotation construction are mutually reinforcing and serve as two-way drivers for each other. On this basis, it proposes future practical approaches, offering a theoretical reference for deepening university educational reform in the new era.